Factors That Influence the Effectiveness of Functional Officials Equalization Work on the Implementation of Bureaucratic Simplification Policy Through Job Satisfaction As An Intervening Variable in Riau Islands Province - Ade Rahmah; Bambang Satriawan; Nolla Puspita Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study, researcher variables, Job Placement, Work Environment, Competency, Job Satisfaction and Work Effectiveness. Data analysis with parametric and non-parametric statistics using SEM-PLS (Structural Equation Modeling-Partial Least Square) Data analysis with parametric and non-parametric statistics regarding research variables, calibration test / pilot test, validity and reliability, Outer model and inner model analysis , as well as a discussion of the results of hypothesis testing or Path Analysis Path. This study uses path analysis to examine the pattern of relationships that reveal the effect of a variable or set of variables on other variables, both direct and indirect. The calculation of the path coefficient in this study is assisted by SmartPLS Ver 4.0 2022. The results of this study indicate a direct influence that Job Placement, Work Environment and Competence variables have a significant positive influence on Job Satisfaction. Job satisfaction has a positive but insignificant influence. Job Placement and competence have a significant positive influence on Work Effectiveness. Work Environment has a positive but insignificant influence on Work Effectiveness. The results of the study for indirect influence where Job Satisfaction has a positive and insignificant influence in mediating the influence of Job Placement, Work Environment and Competence on Work Effectiveness.